2014
DOI: 10.4049/jimmunol.1302850
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of TLR2-Mediated Antigen Cross-Presentation in Dendritic Cells

Abstract: Cross-presentation is a key function of dendritic cells (DCs), which present exogenous Ags on MHC class I molecules to prime CTL responses. The effects of TLR triggering on the cross-presentation of exogenous Ags by DCs remain unclear. In this study, we used synthetic dipalmitoylated peptides and TLR2 agonist–conjugated peptides as models to elucidate the mechanisms of TLR2-mediated cross-presentation. We observed that the internalization of dipalmitoylated peptides by bone marrow–derived DCs was facilitated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Since in the vacuolar pathway the presented peptides must be generated in the endocytic compartment, this pathway may operate in more catabolic endocytic compartments. This idea is consistent with findings that the route of antigen uptake and/or the activation state of the APC may promote vacuolar XPT, as targeting antigen to TLR2 results in peptide-loading of MHC I molecules in later, rab7+ LAMP1+ vesicles (142). …”
Section: Nature Of the Cross Presenting Vesiclessupporting
confidence: 90%
“…Since in the vacuolar pathway the presented peptides must be generated in the endocytic compartment, this pathway may operate in more catabolic endocytic compartments. This idea is consistent with findings that the route of antigen uptake and/or the activation state of the APC may promote vacuolar XPT, as targeting antigen to TLR2 results in peptide-loading of MHC I molecules in later, rab7+ LAMP1+ vesicles (142). …”
Section: Nature Of the Cross Presenting Vesiclessupporting
confidence: 90%
“…It has been reported that TLR7 and TLR9 ligands induced inflammations are inhibited by CQ/HCQ in macrophages [48,49]. CQ inhibits TLR3-induced biological response and TLR2-mediated antigen cross-presentation in immune cells [50,51]. Inflammation plays indispensible role in the pathogenesis of CAC, including TLRs [3,52].…”
Section: Discussionmentioning
confidence: 99%
“…Toll‐like receptor 2 evokes cross‐presentation secondary to activation of the MyD88 pathway . MyD88 conforms a fundamental pathway inducing inflammation.…”
Section: Pattern Recognition Receptors In Antigen‐presenting Dcs and mentioning
confidence: 99%